(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the structural characteristics and semantic features of nominal phraseological units as an essential component of the phraseological system of the English language. Nominal phraseological units are analyzed as fixed or semi-fixed word combinations that function syntactically as nouns and possess completely or partially reinterpreted meanings. The study focuses on their grammatical structure, stability, and reproducibility, which distinguish them from free word combinations. Special attention is paid to semantic properties such as idiomaticity, semantic integrity, evaluative meaning, and cultural specificity. The article draws on the theoretical framework of phraseological studies developed by A. V. Kunin and other prominent linguists. The analysis demonstrates that nominal phraseological units serve as expressive and cognitive tools in discourse, reflecting national culture and collective experience while enhancing communicative efficiency. The findings contribute to a deeper understanding of the interaction between structure and meaning in phraseology and underline the importance of nominal phraseological units in linguistic research.